2023
DOI: 10.1002/cam4.5531
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidinase‐like 2 can serve as a novel therapeutic target and prognostic biomarker in acute myeloid leukemia

Abstract: Background Identifying therapeutic targets and prognostic biomarkers significantly contributes to individualized treatment of acute myeloid leukemia (AML). Dihydropyrimidinase‐like 2 (DPYSL2) expression was decreased in homoharringtonine (HHT)‐resistant AML cells, which were established by our group. DPYSL2 plays an important role in axon growth and has oncogene effect in glioblastoma. However, little research has been conducted to investigate the function of DPYSL2 in AML pathogenesis. Methods Auto‐docking wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…DPYSL2, also known as CRMP2, is a collapsin response mediator protein, whose physiological function is to primarily regulate axonal growth. Recent studies have revealed that DPYSL2 is more highly expressed in human colorectal cancer, non‐small cell lung cancer, bladder cancer, and acute myeloid leukemia (AML) than in normal tissues and may serve as a prognostic biomarker 34–37 . In vitro and in vivo experiments on DPYSL2 showed that it promotes the proliferation, migration, and invasive abilities of bladder cancer cells by regulating aerobic glycolysis and EMT through pyruvate kinase M2 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DPYSL2, also known as CRMP2, is a collapsin response mediator protein, whose physiological function is to primarily regulate axonal growth. Recent studies have revealed that DPYSL2 is more highly expressed in human colorectal cancer, non‐small cell lung cancer, bladder cancer, and acute myeloid leukemia (AML) than in normal tissues and may serve as a prognostic biomarker 34–37 . In vitro and in vivo experiments on DPYSL2 showed that it promotes the proliferation, migration, and invasive abilities of bladder cancer cells by regulating aerobic glycolysis and EMT through pyruvate kinase M2 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between DPYSL2 and Janus kinase 1 was shown to promote the migration of breast cancer cells by regulating the signal transducer and activator of transcription 3 (STAT3)/vimentin pathway 38 . Furthermore, the inhibition of DPYSL2 suppresses AML cell growth and promotes apoptosis via the JAK2/STAT3/5 and PI3K P85/AKT/GSK3β pathways 37 . Thus, DPYSL2 may play an oncogenic role in tumors, and future studies should explore whether miR‐145‐5p can directly regulate the expression of DPYSL2 and affect the function of UTUC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to discover novel biomarkers to better understand the molecular basis of AML. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%